Non-invasive bladder cancer detection by fluorescent in situ hybridization on urine samples: Fluorescentna in situ hibridizacija kot neinvazivna tehnika odkrivanja raka mehurja v vzorcih urina - Kokalj-Vokač, Nadja; Hajdinjak, Tine; Zagorac, Andreja; Erjavec-Škerget, Alenka; Kavalar, Rajko (Acta Medico-Biotechnica, 2021)
Purpose: To evaluate the diagnostic accuracy of the UroVysion FISH test for detecting transitional cell bladder cancer on a mixed sample of urological patients.Methods: Urine samples were collected from patients before cystoscopy. In the case of tumor identification, transurethral resection and histological verification were performed. The fluorescent in situ hybridisation (FISH), using a commercial kit (UroVysion) containing hybridization probes for chromosomes 3, 7, 17, and 9p21, was used. At least 25 morphologically abnormal cells or all cells present on the slides were analyzed.Results: Of 179 samples, 1 was infected and in 35 (20%), no cells were identified. Test sensitivity was 76.2% (95% CI 52.8–91.8) and specificity 93.6% (95% CI 88.6–96.9); as compared to the data in the literature, this result was considered significant. Most tumors had numerical chromosome aberrations. The prevalence of histologically, which verified tumors, was 11.8%.Conclusion: Price and time–consuming procedures are major obstacles for use of the UroVysion FISH test. However, neither cytology nor UroVysion FISH are 100% specific. Higher sensitivity compared to cytology, which is evident not only in case of superficial, but also of invasive tumors (like T1) and its ability to provide numerical results, are advantages which may make UroVysion FISH test useful. Thus, this test has potential for future use. cells were identified. Test sensitivity was 76.2% (95% CI 52.8–91.8) and specificity
Keywords: bladder neoplasms; sensitivity and specificity; fluorescence in situ hybridization; genetic markers